2006
DOI: 10.1007/s10495-006-0487-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased ROS generation and p53 activation in α-lipoic acid-induced apoptosis of hepatoma cells

Abstract: Alpha-lipoic acid (alpha-LA) is an antioxidant used for the treatment of a variety of diseases, including liver cirrhosis, heavy metal poisoining, and diabetic polyneuropathy. In addition to its protective effect against oxidative stress, alpha-LA induces apoptosis in different cancer cells types. However, whether alpha-LA acid induces apoptosis of hepatoma cells is unknown. Herein, we investigated whether alpha-LA induces apoptosis in two different hepatoma cell lines FaO and HepG2. The results showed that al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
105
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(122 citation statements)
references
References 58 publications
14
105
0
3
Order By: Relevance
“…In support of our results, long time exposure to ALA results in increase of lipid peroxidation, mitochondrial damage and inhibition of glycogen synthesis [17,36]. Also, it has been shown that high dose of ALA could arrest cell cycles in some cells [35,55] or could provoke cell death through internucleosomal DNA fragmentation and caspase cleavage in numerous cancer cell lines [48,55,57]. Hence, it appears that high doses of ALA more than 100 uM are toxic for isolated preantral follicles.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In support of our results, long time exposure to ALA results in increase of lipid peroxidation, mitochondrial damage and inhibition of glycogen synthesis [17,36]. Also, it has been shown that high dose of ALA could arrest cell cycles in some cells [35,55] or could provoke cell death through internucleosomal DNA fragmentation and caspase cleavage in numerous cancer cell lines [48,55,57]. Hence, it appears that high doses of ALA more than 100 uM are toxic for isolated preantral follicles.…”
Section: Discussionsupporting
confidence: 85%
“…This observation may give explanation about our finding which why increasing of ALA concentrations results in decrease developmental competence of isolated follicles. In addition, as previous mentioned, high dose of ALA in numerous cancers cell lines could induce apoptosis [35,48,55,57] which explicates, high degeneration rate of follicles in the presence of high concentrations of ALA.…”
Section: Discussionmentioning
confidence: 61%
“…Hsin et al (2008) found that nano silverinduced apoptosis was mediated by the ROS via JNK and p53 activation. ROS could also directly activate p53, most probably by the induction of DNA damage (Simbula et al 2007;Turkez and Togar 2010;Turkez and Geyikoglu 2010;Turkez et al 2012). Based on the results of Liu and Sun (2010), the following silica nanoparticles-mediated signaling pathways for apoptosis related events were proposed as ROS production (JNK/c-Jun phosphorylation), P53 activation, Bax up regulation and Bcl-2 down regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The dramatic increase in ROS levels and the disruption of the antioxidant balance result in oxidative damage to cellular structures, signal transduction www.chinaphar.com Lu C et al Acta Pharmacologica Sinica npg changes and cell death [29] . Many studies have reported that ROS induce apoptosis in various cancer cells [30][31][32] . Our experiments demonstrated that RIP3 gene transfection enhanced the PTL-induced generation of intracellular ROS in MCF-7 and MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 99%